The complete sequence and gene organization of the short unique region of herpesvirus of turkeys - Zelnik, V.; Darteil, R.; Audonnet, J. C.; Smith, G. D.; Riviere, M.; Pastorek, J.; Ross, L. J. N. (Journal of General Virology, 1993)
The DNA sequence of the whole of the short unique region (U S ) and that of part of the short terminal repeat (TR S ) of herpesvirus of turkeys (HVT) were determined. HVT U S is 8.6 kbp long and contains eight potential open reading frames (ORFs). Seven of these have counterparts in the U S of herpes simplex virus type 1 (HSV-1). The homologous proteins include US1, US2, US10, protein kinase (US3) and the glycoproteins gD, gI and gE. In addition, HVT contains one ORF which has a counterpart in the U S of Marek’s disease virus (MDV) but is not homologous to any other known herpesvirus gene. Although HVT and MDV proteins encoded by U S genes have evident similarities with proteins encoded by alphaherpesviruses, multiple alignment analysis of predicted amino acid sequences show that HVT proteins are more closely related to MDV proteins than to homologous proteins of mammalian alphaherpesviruses. The percentage amino acid identity between HVT and MDV U S -encoded proteins ranges from 35 to 65, the most conserved protein being encoded by the homologues of the HSV-1 US2 gene. Most of the genes are collinear with those of HSV-1 except US10 which is transposed in HVT and MDV. A characteristic feature of HVT is the fact that approximately two-thirds of the gE gene is located in the inverted repeats flanking U S .